Groundwater arsenic remediation treatment technology and scale up - Pal, Parimal (Butterworth Heinemann is an imprint of Elsevier, 2015)
[This book] provides the latest breakthrough groundwater treatment technologies and modelling and simulation methods for project scale up and eventually field deployment in locations which lack the proper central water distribution system to ensure arsenic free groundwater.